Respuesta :
Answer:
X = -4 Y =2
Step-by-step explanation:
3X+5Y=-2
-X+2Y=8
I will use elimination. Multiply the second equation by 3 to eliminate x
3(-X+2Y)=8*3
-3X +6Y = 24
Add this to the first equation
3X+5Y=-2
-3X +6Y = 24
--------------------
11Y = 22
Divide by 11
11Y/11 = 22/11
Y =2
Now we need to find X
-X+2Y=8
-X +2(2) = 8
-X +4 = 8
Subtract 4 from each side
-X +4-4 = 8-4
-X = 4
Multiply by -1
X = -4
3x + 5y = -2
-x + 2y = 8
Multiply second equation by 3 and add to the first:
-3x + 6y = 24
11y = 22
y = 2
x = 2y - 8 = -4
Check:
3(-4) + 5(2) = -12 + 10 = -2 good
-(-4) + 2(2) = 8 good
Answer: x=-4, y=2